The collected writings of John Maynard Keynes, Volume 4, A tract on monetary reform - Keynes, John Maynard 1883-1946 (The collected writings of John Maynard Keynes, 2013)
Once the urgent problems of reparations, which had deeply troubled Keynes at the Peace Conference at Versailles, were on their way towards solution, Keynes turned to the equally grave problems of the currencies of Europe and their adjustment to the post-war world. These issues had been discussed in the series of Reconstruction Supplements of the Manchester Guardian Commercial that he had edited during 1922. In the Tract Keynes drew heavily on his own contributions to that series. This edition makes available the variations between the texts. The Tract remains of interest in three respects. First, it shows the state of Keynes's thinking about monetary problems and the causes of inflation in the early 1920s. Second, it provides one of the clearest expositions ever written of the determination of forward exchange rates. Third, it shows Keynes already favouring flexible exchange rates as a means of allowing independence in national economic policy